The SlDOF9‐SlSWEET17 Module: a Switch for Controlling Sugar Distribution Between Nematode Induced Galls and Roots in Tomato - Xiaoyun Wang; Zhimei Wang; Xinyue Tang; Jiamei Qin; Xiaoxuan Zhou; Lixia Gu; Huihui Bian; Lulu Sun; Huang Huang; Rui Yang; Jianli Wang; Shaohui Wang; et al. (Advanced Science)
Abstract In the complex interactions between plants and pathogens, the regulation of nutrient allocation plays a critical role in determining plant health and susceptibility to diseases. Root‐knot nematodes (RKNs, Meloidogyne incognita) extract sugar from plants during their interactions with the hosts. SWEET (Sugars Will Eventually be Exported Transporters) proteins are a class of non‐energy‐consuming sugar uniporters that regulate the allocation of sugars in plant. Here, it is find that SlSWEET17 (Solanum lycopersicum SWEET17), a member of the SWEET family in tomato, is localized to the plasma membrane, Golgi body and small vacuoles, and is highly expressed in galls. Further studies show that SlSWEET17 negatively regulates the sugar transport capacity of other SlSWEETs via protein interactions. Overexpression of SlSWEET17 significantly decreases the soluble sugar content in galls and susceptibility to RKNs, while SlSWEET17 knockout‐mutation (ko‐mutation) has the opposite effect. It is also identified SlDOF9 (Solanum lycopersicum DNA binding with one finger 9), an upstream negative regulator of SlSWEET17, using ChIP (chromatin immunoprecipitation) analysis, electrophoretic mobility shift assays and dual‐Luciferase assays. SlDOF9‐overexpressing plants show increased sugar content in galls and susceptibility to RKNs, and sldof9cr ko‐mutants have the opposite phenotype. This results show how SlDOF9‐SlSWEET17 affects RKN infection through sugar partitioning from roots to galls.